EVALUATION THE ANTINOCICEPTIVE EFFECTS OF METOCLOPRAMIDE AND THEIR INTERACTION WITH DIPHENHYDRAMINE IN ACUTE MODEL OF PAIN IN MALE MICE - Taimaa A. Al-Najmawy; G. A-M. Faris (Basrah Journal of Veterinary Research)
The aim of this study was to evaluate the analgesic effect of metoclopramidealone or as a combination with diphenhydramine. The type of interaction between twodrugs also determined at level of acute pain centrally and peripherally using hot-plateand writhing test in male mice. The individual ED50 value of metoclopramide anddiphenhydramine for induction of antinociceptive effect was at 30.7 mg/kg,ip and0.57mg/kg, sc ,respectively. While combined this ED50 value of diphenhydramine andmetoclopramide at several ratios (1:1, 0.5:1, 0.5:0.5 and 0.25:1) respectively,produced synergism interaction between two drugs at all ratios (except the final ratio,produced antagonism). This combination decreased the ED50 of each drug andproduced good antinociceptive effect in male mice at centrally level. Concomitantadministration of metoclopramide ip and diphenhydramine sc at double doses of ED50for each drug, also produced good analgesic effect at visceral pain level, whichinduced by acetic acid in writhing test. Avery effective and safe antinociceptive effectand also achieved using combination of metoclopramide and diphenhydramine atsedative doses (not analgesic).The results suggested that synergism (super-additive)interaction of diphenhydramine and metoclopramide combination was a good and safeantinociceptive effect produced by a combination of sedative dose for each drug . Thecombination of these drugs very important in practice of the veterinary medicine.